PERILAKU MASYARAKAT DALAM PENCEGAHAN PENULARAN SCHISTOSOMIASIS DI DESA MEKAR SARI KABUPATEN POSO - I Kadek Wartana; Gustini Gustini; Estelle Lilian Mua; Veni Mornalita Kolupe; Robi A. Sekeon (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
ABSTRACT The high incidence of schistosomiasis in snails (2.56%) in Central Sulawesi can increase the risk of transmission to humans. Reducing cases of schistosomiasis infection in humans can be done by involving the community in schistosomiasis prevention programs which can lead to increased behavior and awareness about schistosomiasis prevention. This study used a quantitative design with a cross-sectional approach which took the research location in Mekar Sari Village, Poso Regency. The study population totaled 369 heads of families (KK) with a total sample of 80 families taken by proportional random sampling. Data collection tool using a questionnaire. Data were analyzed univariately and bivariately using the chi-square test with a 95% confidence level. The results showed that 72.9% of respondents had high knowledge, 58.8% of respondents had a positive attitude, and 65% of respondents had good behavior in preventing transmission of schistosomiasis. The results of the chi-square test obtained a p value for knowledge of 0.027 and for attitude of 0.005 (p value <0.05), so that it can be concluded that knowledge and attitudes are significantly related to the behavior of preventing schistosomiasis transmission in Mekar Sari Village, Poso Regency. Keywords: Knowledge, Attitude, Behavior, Schistosomiasis